On objective assessment of convergence and precipitation by dynamic trajectory method - BANERJI, S.; RAO , D.V.L.N.; KUNDRA, M.D. (MAUSAM, 1970)
Dynamic trajectories are drawn for intervals of three hours by means of arc-strike technique developed by Good-year and later used by Peterson and others. The wind field required for this purpose is obtained on the basis of streamline analysis at 0.6 km level, while the geostrophic winds have been evaluated from the sea level charts. A fairly accurate idea of areas of low level convergence can be had with the help of these trajectories. An estimation of moisture inflow into the convergence area is made by the use of an empirical relation involving the computation of precipitable water, and average wind-speed normal to the line of maximum curvature; In order to reduce time on computations, they were done on polar coordinates and a nomogram was also prepared for different latitudes for direct application on the polar diagram. The results obtained in a few cases are presented here, which show that some improvement is obtainable by using the stream line analysis, particularly in view of the sparse aerological network.